Rhodnius barretti, a new species of Triatominae (Hemiptera: Reduviidae) from western Amazonia (2013)
ABSTRACT: Rhodnius barretti, a new triatomine species, is described based on adult specimens collected in rainforest environments within the Napo ecoregion of western Amazonia (Colombia and Ecuador). R. barretti resembles Rhodnius robustus s.l., but mitochondrial cytochrome b gene sequences reveal that it is a strongly divergent member of the “robustus lineage”, i.e., basal to the clade encompassing Rhodnius nasutus, Rhodnius neglectus, Rhodnius prolixus and five members of the R. robustus species complex. Morphometric analyses also reveal consistent divergence from R. robustus s.l., including head and, as previously shown, wing shape and the length ratios of some anatomical structures. R. barretti occurs, often at high densities, in Attalea butyracea and Oenocarpus bataua palms. It is strikingly aggressive and adults may invade houses flying from peridomestic palms. R. barretti must therefore be regarded as a potential Trypanosoma cruzi vector in the Napo ecoregion, where Chagas disease is endemic.